Effect of Valproate on Thyroid Gland Function in Children with Epilepsy - Saif Hamed Farhaan; Mohammed, Mohammed Ali; Mohammed, Ahmed Mundher (Academic Journal of Clinicians, 2025)
Background: Epilepsy is the fourth most common neurologic disease, following migraine, stroke, and Alzheimer-related dementia. the primary treatment is the use of anticonvulsant drugs; valproate is an effective anticonvulsant that is widely used for the management of focal and generalized epilepsy. It was approved for use in 1978, although it is well tolerated many sides effect have been reported. Objective: To study the effect of valproate drug on thyroid function in epileptic children. Patients and methods: This cross-sectional study looking for thyroid function status in two cross sections, one is the valproate group (epileptic children used valproate) and a second healthy group age and sex matched (not used valproate and not having epilepsy). The study was conducted and included seventy two children , among them 36 were epileptic children treated with valproate (valproate group) and 36 were healthy children ( healthy group ) , who met the inclusion criteria , who were interviewed using questionnaire, during first of January till the first of December 2018 , in ( Epileptic Clinic in Baghdad Teaching Hospital) , ( Pediatric Neurology Clinic and Ward in Children Welfare Teaching Hospital ) and ( General Pediatric Clinic in Children Welfare Teaching Hospital) in Medical City Directorate , We compared the two group (valproate group and healthy group) by some variables studied include thyroid stimulating hormone , Thyroxine and triiodothyronine . Then we did compare in valproate group according to the change of result in thyroid function test by following variables age, sex, type of epilepsy (focal or generalized), duration of valproate, dose of valproate. Result: This study has enrolled 36 children known to have epilepsy on valproate treatment and age and sex matched 36 healthy children as a healthy group. according to thyroid function test there’s significant increase in thyroid stimulating hormone in valproate group while none of healthy group was having elevated thyroid stimulating hormone. Thyroxine and triiodothyronine stay within normal reference for both groups. Duration of treatment with valproate more than 24 months have a significant value in increase thyroid stimulating hormone in valproate group, while other variables age, sex, type of epilepsy and dose of valproate didn’t have significant value in increase thyroid stimulating hormone in valproate group. Conclusion: subclinical hypothyroidism can occur in epileptic children treated with valproate for long duration more than 24 months.